2015
DOI: 10.1176/appi.neuropsych.14070157
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Frontotemporal Dementia From Catatonia: A Complex Neuropsychiatric Challenge

Abstract: Symptoms of catatonia, 1 including stereotypy, echophenomena, mutism, and perseveration, may overlap with those of behavioral variant frontotemporal dementia (bvFTD), which can lead to mistaken diagnoses. 2,3 In addition, catatonia can also be a presenting symptom of bvFTD. 4 We report a case with a complex differential diagnosis between persistent residual catatonia symptoms and bvFTD, and we review the approach to this neuropsychiatric challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…30 Indeed, a number of catatonic symptoms may overlap with those of the behavioral variant of FTD. 31 Catatonia has also been described as a manifestation of FTD. 32 In our sample, the diagnostic distribution was similar in responders and non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…30 Indeed, a number of catatonic symptoms may overlap with those of the behavioral variant of FTD. 31 Catatonia has also been described as a manifestation of FTD. 32 In our sample, the diagnostic distribution was similar in responders and non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the association between bvFTD and FTLD‐TDP type C has not been shown, so this case would be atypical in that regard. Several cases of clinical FTD with catatonic syndrome have been reported . but these were not pathologically examined.…”
Section: Discussionmentioning
confidence: 99%
“…10 case report, authors reported catatonia in psychiatric disorders as being more frequently characterized by a fluctuating trend and usually responding to Lorazepam. In contrast, when catatonia was present in bvFTD, progressive and irreversible deterioration were more common [41].…”
Section: Clinical Characteristics Orienting Differential Diagnosismentioning
confidence: 95%
“…Catatonia, a clinical presentation classically associated with SCZ, is nowadays considered a specifier applicable to different psychiatric and neurological disorders (DSM-5) and could be described as a manifestation in FTD patients. Some symptoms such as stereotypy, echophenomena, mutism, and perseveration arise both in bvFTD and in catatonia [39][40][41][42]. Moreover, some case series reported catatonia as the first clinical presentation in FTD patients [43,44].…”
Section: Clinical Characteristics Orienting Differential Diagnosismentioning
confidence: 99%